Efektivitas Pelayanan Saat Pandemi Covid-19 di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Lima Puluh Kota - Nikita Amelia (PUBLICNESS: Journal of Public Administration studies, 2022)
Effectiveness is the relationship between output and goals or objectives to be achieved. The definition of effectiveness is basically related to the achievement of policy goals or targets. Operational activities are said to be effective if the process of these activities achieves the final policy goals and objectives (spending wisely) Mahsun added that effectiveness is a measure of the success or failure of an organization to achieve its goals. If an organization succeeds in achieving its goals, then the organization is said to have been running effectively (Mahsun 2006: 182). Effectiveness is assessed using 8 indicators according to P. Siagian, namely, the first is the clarity of the goals to be achieved, the second is the clarity of the strategy for achieving the goals, the third is the analysis and formulation of a solid policy, the fourth is careful planning, the fifth is the preparation of the right program, the sixth is namely the availability of work facilities and infrastructure, Seventh, namely effective and efficient implementation, Eighth, namely an educational supervision and control system. Mahsun added that effectiveness is a measure of the success or failure of an organization to achieve its goals. If an organization succeeds in achieving its goals, then the organization is said to have been running effectively